2022
DOI: 10.3389/fneur.2022.948204
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective real-world pilot data on transcranial pulse stimulation in mild to severe Alzheimer's patients

Abstract: IntroductionTranscranial pulse stimulation (TPS) is a non-invasive neuromodulation therapy that uses short, repetitive shockwaves through a neuro-navigated device. Current research suggests that these pulses lead to a wide range of vascular, metabolic, and neurotrophic changes. This relatively new CE-marked treatment provided first promising results in a clinical pilot study for improving cognition in mild-to-moderate Alzheimer's. Data from other centers is lacking, so here we analyzed safety and pilot real-wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Only the study by Cont et al 26 reported the ADAS total score, ADAS cognitive score, MMSE, and MoCA. Compared to baseline, TPS significantly increased the ADAS total score and ADAS cognitive score in patients with AD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only the study by Cont et al 26 reported the ADAS total score, ADAS cognitive score, MMSE, and MoCA. Compared to baseline, TPS significantly increased the ADAS total score and ADAS cognitive score in patients with AD.…”
Section: Resultsmentioning
confidence: 99%
“…The ADAS is generally more sensitive than the MMSE and MoCA scales. 34 , 35 , 36 Cont et al 26 performed a subgroup analysis of patients with AD of varying severity and found that TPS improved more in the group with moderate and severe cognitive impairment than in the group with mild cognitive impairment across all cognitive assessments. This suggests the need to consider a ceiling effect of TPS on mildly affected patients with AD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors pointed out that treatment of different brain regions along with the effect of MRgFUS on AD needs to be properly characterized [31]. In addition, recent clinical AD studies based on transcranial pulsed stimulation (TPS), which consists of short (3 µs), repetitive ultrasound shockwaves, reported scarce side effects as well as improvement in the Alzheimer's disease Assessment Scale (ADAS) and the ADAS cognitive scores [32], and improvement of depression scores (BDI-II) accompanied by effects in functional connectivity after one session of TPS [33]. Furthermore, TPS enabled induction of neuroplasticity changes up to one week after the last stimulation within a three-week experimental longitudinal protocol [34].…”
Section: Alzheimer's Diseasementioning
confidence: 99%